2019
DOI: 10.1371/journal.pone.0219363
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity enhances CDDP-induced apoptosis signal via p53-independent mechanisms in cancer cells

Abstract: Although the biological systems in the human body are affected by the earth’s gravity, information about the underlying molecular mechanisms is limited. For example, apoptotic signaling is enhanced in cancer cells subjected to microgravity. We reasoned that signaling regulated by p53 may be involved because of its role in apoptosis. Therefore, we aimed to clarify the molecular mechanisms of modified cis-diamminedichloroplatinum (CDDP)-sensitivity under simulated microgravity by focusing on p53-related cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Space research and investigations on cell signaling processes in the growth and development of cells exposed to microgravity (µg) is currently a hot topic in cancer research and regenerative medicine [1][2][3][4][5]. Prostate cancer is the fifth leading cause of cancer mortality in men, with the second highest cancer incidence worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Space research and investigations on cell signaling processes in the growth and development of cells exposed to microgravity (µg) is currently a hot topic in cancer research and regenerative medicine [1][2][3][4][5]. Prostate cancer is the fifth leading cause of cancer mortality in men, with the second highest cancer incidence worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that simulated microgravity altered the cytoskeleton and nuclear positioning, leading to enhanced cell apoptosis via suppressing the focal adhesion kinase (FAK)/RhoA-controlled mammalian target of rapamycin complex 1 (mTORC1)/nuclear factor-kappa B (NF-κB) and extracellular signal-regulated kinase1 (ERK1/2) pathways [44]. Elsewhere, microgravity altered cis-diamminedichloride platinum (II) (CDDP) sensitivity through the activation of caspase-3 by a p53-independent mechanism in the hepatoblastoma cell line, HepG2 [20]. Microgravity decreased the levels of mTOR and increased the microtubule-associated protein light chain 3-II/I ratio (LC3), suggesting the activation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Microgravity decreased the levels of mTOR and increased the microtubule-associated protein light chain 3-II/I ratio (LC3), suggesting the activation of autophagy. Disturbed immune function in microgravity could be a consequence of ICAM-1 modulation in the monocyte/macrophage system, which, in turn, could have a strong impact on the cells' interaction with T-lymphocytes and migration [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of an anti-apoptotic protein, BCL-2, BNIP3 and induction of the apoptosis-related proteins, p53, PARP and BAX in ML-1 thyroid cancer cells has been demonstrated, through the simulated microgravity condition [7]. Tumor antigen p53 responds to stimulated microgravity by induction of downstream proteins such as p21, MDM2 and BAX, which regulate the cell cycle and apoptosis [8]. Apoptosis of thyroid cancer cell lines ML-1 and ONCO-DG1 increased after 24 h exposure to microgravity [9], whereas apoptosis in MDA-MB-231 breast cancer and SGC-7901 gastric adenocarcinoma cells showed increase after 72 h of exposure [10,11].…”
Section: Effect Of Microgravity On the Functioning Of Cancer Cell: Efmentioning
confidence: 99%